PpEG4 is a peach endo-beta-1,4-glucanase gene whose expression in climacteric peaches does not follow a climacteric pattern - Trainotti, Livio (Journal of experimental botany, 2006)
In peach (Prunus persica L. Batsch.) the degradation of the pectic compounds of the cell wall is considered to be the principal component responsible for fruit softening. Many genes encoding enzymes acting on the different polymers of the pectic matrix have been shown to be highly expressed during the late phases of softening, with polygalacturonase being the most important. Nevertheless, it is known that softening starts well before the ethylene climacteric rise which occurs concomitant with the maximal expression of the pectolytic enzymes. The cloning and characterization of PpEG4, an endo-beta-1,4-glucanase (EGase) gene preferentially expressed in preclimacteric fruits, are presented here. PpEG4 belongs to the group of EGases containing, at their carboxy-terminus, a peptide similar to the cellulose binding domain of microbial origin. This EGase is also expressed during abscission of both leaves and fruits. The effect of exogenous ethylene treatments on PpEG4 transcription is null in young fruits and negative in preclimacteric ones, while it is positive in abscission zones. Thus, the expression of PpEG4 seems to be more dependent on the type of separation process rather than being influenced by a direct hormone action. The ability of the PpEG4 regulatory sequences to drive transcription in cells undergoing separation events is also maintained in tomato, where about 3 kb of the gene promoter could drive the expression of gusA in preclimacteric fruits and in the fruit abscission zones